Non-contact and contact measurement system for detecting projectile position in electromagnetic launch bore. (20th November 2017) - Xu, Weidong; Yuan, Weiqun; Xu, Rong; Zhao, Hui; Cheng, Wenping; Zhang, Dongdong; Zhao, Ying; Yan, Ping
Abstract: This paper introduces a new measurement system for measuring the position of a projectile within a rapid fire electromagnetic launching system. The measurement system contains both non-contact laser shading and metal fiber contact measurement devices. Two projectiles are placed in the rapid fire electromagnetic launch bore, one in the main accelerating segment and the other in the pre-loading segment. The projectile placed in the main accelerating segment should be shot first, and then the other is loaded into the main segment from the pre-loading segment. The main driving current ( I -main ) can only be discharged again when the second projectile has arrived at the key position (the projectile position corresponds to the discharging time) in the main accelerating segment. So, it is important to be able to detect when the second projectile arrives at the key position in the main accelerating segment. The B-dot probe is the most widely used system for detecting the position of the projectile in the electromagnetic launch bore. However, the B-dot signal is affected by the driving current amplitude and the projectile velocity. There is no current in the main accelerating segment when the second projectile moves into this segment in rapid fire mode, so the B-dot signal for detecting the key position is invalid. Due to the presence of a high-intensity magnetic field, a high current, a high-temperature aluminum attachment, smoke and strong vibrations, it is very difficult to detect the projectile position in the bore accurately. So, other measurements need to be researched and developed in order to achieve high reliability. A measurement system based on a laser (non-contact) and metal fibers (contact) has been designed, and the integrated output signal based on this detector is described in the following paper.